Aerobic Heterotrophic Bacteria Indigenous to pH 2.8 Acid Mine Water: Predominant Slime-Producing Bacteria in Acid Streamers - Dugan, Patrick R. (1970)
Five gram-negative bacteria, two gram-positive bacteria, and one yeast were isolated from “acid streamers” taken from acid mine water. One gram-positive rod which has been tentatively identified as a Bacillus species appeared to be the predominant organism in the streamers. This isolate produced copious amounts of extracellular polymer at 10 C in the laboratory and was considered to be the primary source of polymer in the “acid streamer” slime matrix. The organism grew slowly at pH 2.8 in mine water media, but the optimal pH was approximately 7.0.